The Effect of Aerobic Exercise Frequency on Reducing Blood Glucose in Type 2 Diabetes Mellitus Sufferers in the Lingsar Health Center Working Area in 2024 - Fathoni, Akhmad; Sentana, Aan Dwi; Ningsih, Mira Utami; Rifki, Muhammad (Poltekita: Jurnal Ilmu Kesehatan, 2024)
One of the keys to a person suffering from diabetes mellitus being able to live a healthy life like other people without diabetes is to maintain balanced blood glucose levels within normal limits. One important way to reduce blood glucose levels, especially in type 2 DM sufferers, is exercise. This study aims to identify the effect of aerobic exercise, on changes in blood glucose levels. This research is a pre-experimental research with a one group pre-posttest approach. The research sample was 33 people suffering from type 2 DM at the Lingsar Community Health Center, selected using a simple random sampling technique. Each respondent was given aerobic exercise 3 times a week with a minimum duration of 20 minutes. Data on blood glucose levels before and after the intervention were collected using an observation sheet. The results of the study showed that the average blood glucose before the intervention was 162.2 mg/dL and after the intervention it fell to 156.14 mg/dL. The t-test with a=0.05 showed r=0.000. It can be concluded that there is an effect of aerobic exercise on the respondents' blood glucose levels. Aerobic exercise has been proven to reduce the average blood glucose level after this is done regularly. This study results can be an evidenced base for community nursing to promote regular aerobic exercise among people with DM, to help reduce or control their blood glucose.